FUZZY COLORING OF FUZZY PATHS USING MATLAB - M.G. Karunambigai; Jessalet Ann Mathew (IJRDO -JOURNAL OF MATHEMATICS, 2025)
This paper determines the chromatic number of fuzzy paths and its middle graphs using a fuzzy coloring procedure implemented in MATLAB. The study applies proper fuzzy coloring and provides computational verification through graphical visualization